Teacher Challenges in Implementing the Independent Curriculum at SMP N 3 Palembayan - Hasibuan, Muhammad Arif; Kardena, Absharini (Lembaga Yasin AlSys, 2024)
As time goes by, the challenges and roles carried out by teachers will of course also change, one of the factors is developments in the field of technology which also play a role and can influence these changes. Especially when referring to various policies in the existing and newest curriculum, this is certainly an interesting thing to discuss. Therefore, the author's aim in this article is to discuss the challenges and role of the teacher himself, especially in dealing with the use of the independent learning curriculum, which is the newest curriculum and will be implemented in the future. Then related to the data sources used are various forms of literature which are of course related to the theme, whether in the form of books, articles, journals and other written sources on the internet. For the writing itself, the author uses the library research method by searching for and collecting relevant data sources, then filtering the sources that have been collected so that the sources that are most relevant to the theme to be studied or raised can be found, then make conclusions and record various important things from existing sources, and only then will they be implemented in written form.